Використання засобів інформаційно-комунікаційних технологій при навчанні фізики студентів інженерних спеціальностей - Сосницька, Наталя Леонідівна; Сосницкая, Наталья Леонидовна; Sosnytska, Natalia; Дяденчук, Альона Федорівна; Дяденчук, Алена Федоровна; Diadenchuk, Alona (My University, 2021)
UK: Мета дослідження полягає в розробці методик використання засобів ІКТ у процесі навчання фізики студентів інженерних спеціальностей. EN: The paper proposes the introduction of Microsoft Office Excel spreadsheet in the educational process to visualize information in the general course of physics. Examples of the constructed schedules during performance by applicants of higher education of engineering specialties of practical and laboratory works are resulted.The introduction of this approach in the educational process describes significant positive signs.
Keywords: фізика; навчання; інновації; графік; MicrosoftOfficeExcel